2020
DOI: 10.1186/s12966-020-00948-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementation of menu labelling interventions from a food service industry perspective: a mixed methods systematic review

Abstract: Background: Eating outside the home contributes to poor dietary habits worldwide and is associated with increased body fat and weight gain. Evidence shows menu labelling is effective in promoting healthier food choices; however, implementation issues have arisen. The purpose of this systematic review was to synthesise the evidence on the perceived barriers and facilitators to implementation of menu labelling interventions from the perspective of the food service industry.Methods: Peer-reviewed and grey literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 87 publications
2
28
0
Order By: Relevance
“…The use of specific examples of marketing and nudging strategies was not comprehensive of all possible marketing/nudging strategies. A notable gap was discussion of nutrition information on menus, which has been extensively promoted, but for which evidence of effectiveness is limited ( 42 44 ). While additional ideas were elicited during interviews, it is possible that additional strategies were missed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of specific examples of marketing and nudging strategies was not comprehensive of all possible marketing/nudging strategies. A notable gap was discussion of nutrition information on menus, which has been extensively promoted, but for which evidence of effectiveness is limited ( 42 44 ). While additional ideas were elicited during interviews, it is possible that additional strategies were missed.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were presented with 14 specific FV nudging strategies from the literature, as previous work has found that vignettes are helpful in eliciting attitudes and beliefs ( 41 ). It was decided to avoid discussion of nutrition information on menus, as a mainly informational strategy already extensively studied ( 42 44 ). The interview guide was reviewed by the research team and pilot-tested in 1 person.…”
Section: Methodsmentioning
confidence: 99%
“…Menu labeling is one of eight marketing-mix and choice architecture strategies that restaurant businesses can use to nudge customers toward healthy food environments 20 [ 93 , 94 ]. A compelling business case must be made to persuade chain restaurants to adopt these strategies to improve their corporate image and attract new customers who want healthy meals [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Menu labeling is one of eight marketing-mix and choice architecture strategies that restaurant businesses can use to nudge customers toward healthy food environments 20 [93,94]. A compelling business case must be made to persuade chain restaurants to adopt these strategies to improve their corporate image and attract new customers who want healthy meals [95]. Table 5 suggests several actions for stakeholders, including governments, the WHO, restaurant businesses, private foundations, researchers, and civil society organizations to develop, implement, and evaluate comprehensive restaurant menu labeling policies.…”
Section: Implications For Policy Practice and Researchmentioning
confidence: 99%
“…This involves the production and processing of foods from breakfast to dinner for the community across a variety of institutions. There is growing recognition of the importance of providing good quality and nutrient-rich food in institutional settings [ 23 , 24 ], and also an understanding that dietary preferences and needs vary and include vegetarians, vegans, and a wide range of other nutritional conditions, such as food allergies [ 25 ].…”
Section: Introductionmentioning
confidence: 99%